Financial analysis of an installed small scale seasonal thermal energy store. (February 2016) - Colclough, Shane; Griffiths, Philip
Abstract: The financial viability of an installed solar heating system incorporating a Seasonal Thermal Energy Store (STES) for a house constructed to the low-energy Passivhaus standard is analysed. Details are provided of system costs and the recorded performance for the installation which is located in Galway, Ireland, a location which experiences a Temperate Maritime Climate. Using these figures, a financial Life Cycle Analysis has been undertaken to determine the cost effectiveness of the system in providing space heating and domestic hot water. As part of the life cycle cost analysis the effect of the treatment of the terminal value of the STES was considered. The analysis shows that irrespective of the terminal value attached to the STES, the use of solar thermal energy in combination with an STES offered a more favourable business case than the use of electricity for DHW and space heating over the 40 year time period considered. This shows that a direct space heating and DHW system incorporating STES can be economically viable in a Temperate Maritime Climate in the long term. Highlights: A Passivhaus with a STES based Solar Thermal heating system is analysed. Recorded performance figures and system costs are presented. The payback periods for the STES based heating system are presented. The STES system is financially attractive within the 40 year planning horizon. System optimisation would further increase the attractiveness of the system.